Tumor Microenvironment-Responsive Nanoparticles: Promising Cancer PTT Carriers - Sun H; Li Y; Xue M; Feng D (International Journal of Nanomedicine)
Heming Sun,1 Yuebo Li,2,3 Ming Xue,2,3 Dingqing Feng3 1Institute of Clinical Medical Sciences, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of China; 2Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100029, People’s Republic of China; 3Department of Obstetrics and Gynecology, China-Japan Friendship Hospital, Beijing, 100029, People’s Republic of ChinaCorrespondence: Dingqing Feng, Department of Obstetrics and Gynecology, China-Japan Friendship Hospital (Institute of Clinical Medical Sciences), Beijing, 100029, People’s Republic of China, Email fengdingqing@zryhyy.com.cnAbstract: The tumor microenvironment (TME) is often characterized by distinctive features such as hypoxia, low pH, the overexpression of extracellular matrix-degrading enzymes, and increased redox reactions. These attributes create a specialized internal environment that promotes tumor cell survival and proliferation, thereby facilitating tumor development, metastasis, and the emergence of drug resistance. These challenging aspects pose significant hurdles to the efficacy of traditional cancer therapies. However, they also offer unique opportunities for the development of responsive nanomedicines that specifically target the TME to improve treatment outcomes for cancer patients when combined with photothermal therapy (PTT). This review provides an overview of the predominant features of the TME and delves into recent advancements in the field of nanomedicine, with a special focus on TME-responsive nanomedicines. Each type of TME-responsive nanomedicine is reviewed for its potential value in drug delivery in combination with PTT and chemotherapy, which may enable effective multimodal antitumor therapy. Finally, the review discusses the challenges and opportunities associated with the use of TME-responsive nanomaterials in PTT, highlighting the potential for these innovative strategies to overcome current therapeutic limitations and improve patient outcomes. Keywords: tumor microenvironment, photothermal therapy, cancer therapy, nanoparticle